(untitled) (AACINI - International Journal of Industrial Engineering, 2023)
The viability of incorporating cobots in the production line of mozzarella cheese cylinders and bars is analyzed in a SME company dedicated to the production of dairy products. In the current situation, two employees take care of the filling in the final process of the production line through a manual process susceptible to errors due to fatigue or distraction during an uninterrupted 12-hour daily shift. The convenience of incorporating cobots in the packaging task associated with mozzarella cylinders is analyzed through a simulation program, with the cobot being responsible for filling the cylinders, which an operator is then responsible for taking them to the cold chambers for conditioning the product to dispatch. With the details of the manual work times of the operators and automatic work process of the cobot, productivity and efficiency of the finished products are analyzed. The simulation model, in addition to analyzing the entire line production, allows optimizing the number of operators that the production plant needs. Through multiple simulations of different scenarios, confidence intervals of the operation in steady state are built that allow determining a set of indicators that allow its owner to determine the effectiveness and convenience of incorporating a cobot into its production line. The analysis of multiple scenarios allows selecting the best combination of operators and cobots that together produce the best productivity and efficiency results.